1984
DOI: 10.1161/01.res.54.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 5-HT contraction in isolated bovine ventricular coronary arteries. Evidence for transient receptor-operated calcium influx channels.

Abstract: SUMMARY. The effect of serotonin on isometric tension and transmembrane calcium influx was investigated in rings cut from branches of male bovine circumflex and left anterior descending coronary arteries. Responses were compared to those produced by potassium chloride, and to the serotonin contraction produced in rabbit thoracic aorta. Serotonin in bovine ventricular coronary arteries produced a strong, transient contraction, even at a maximum concentration. Contraction did not decline because of serotonin deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…2, the isolated pig and cattle coronary arteries were contracted by histamine. These results were similar to previous reports in pigs (12,13) and cattle (3,14). In pig coronary arteries, removal of the endothelium increased the maximal response and pD2 value of the histamine-induced contraction ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…2, the isolated pig and cattle coronary arteries were contracted by histamine. These results were similar to previous reports in pigs (12,13) and cattle (3,14). In pig coronary arteries, removal of the endothelium increased the maximal response and pD2 value of the histamine-induced contraction ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Histamine has been reported to contract pig and cattle coronary arteries in vitro (3,4,12,13), but there are few data about the subtypes of histamine receptors and whether vascular responses to histamine are endothelium-dependent or not in these species (12,13). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In experiments on tension development of coronary strips, the significant relaxation to norepinephrine (NE) and epinephrine (EP) has been observed in sheep, 4 rabbit, 5 kitten, 6 bovine, 78 and porcine 79 coronary arteries. In contrast with the weak contraction induced by NE, a relatively strong contraction of porcine or bovine coronary artery can be induced by histamine, 10 serotonin, 8 acetylcholine, 9 or excess KC1. 8 -9 Furthermore, it has been reported that canine coronary artery is much more sensitive to organic calcium an- modifications.…”
mentioning
confidence: 86%
“…All studies were conducted on tissue taken from male New Zealand White rabbits (2.2-2.4 kg), using previously described methods (3,4 Isometric Tension. To record isometric tension, we placed each 3 mm long vascular ring across two stainless steel wires in a chamber containing 20 ml of fresh oxygenated PS solution at 370C.…”
Section: Methodsmentioning
confidence: 99%